MODERN TRENDS IN THE DEVELOPMENT OF THE INTERNATIONAL SECURITIES MARKET - Xazratqulov, Aktamjon (Journal of Contemporary World Studies, 2024)
This article talks about the existence of current problems related to the development of the securities market in our republic and ensuring its integration into the international capital market.